Characterization of discontinuous carbon fibre mat produced by hydrodynamic processes - Liu, Zhe (2017)
It is estimated that in 2017 global demand for carbon fibre may be as much as 111 thousand tonnes and with an annual growth rate (AGR) of 10% to 13%, this number will increase to 191 thousand tonnes by 2022. Commercial operations to recover carbon fibre from waste composites are now developing and as more recovered fibre becomes available new applications for recovered fibre are required. Mats with random in-plane fibre orientation can readily be produced using existing commercial processes, however, due to a random fibre orientation distribution, over 100bar is required to achieve 40% fibre volume fraction during moulding. Under this pressure, fibre breakage significantly reduces the mean fibre length and the properties of the composite manufactured. Nonwoven mats made from short carbon fibres which are aligned in a preferential direction can achieve higher fibre volume fractions with lower fibre breakage even at high moulding pressure. A hydrodynamic alignment process has been developed in the University of Nottingham which consists of three stages; dispersing, depositing and dewatering. In this thesis, the influencing factors in the depositing and dewatering processes will be explored. In the depositing process, the dispersed fibre suspension flows through a converging nozzle which can generate the aligned fibre orientation. A careful nozzle design is required to improve the fibre alignment quality. At the same time, a high level of jet stability will help to maintain this aligned orientation. Thus, both experimental work and CFD simulation were used to increase understanding of both the fibre suspension jet stability behaviour and the effects of nozzle shape on fibre orientation. When the fibre suspension jet is depositing, many processing factors (e.g. fibre length, fibre volume concentration, dewatering vacuum level) will affect the fibre orientation on the mat. A series of experimental work was undertaken following a 2-level full factorial experiment design. Furthermore, a composite of 46% fibre volume fraction has been produced moulded at a pressure of just 7 bar in an autoclave, exhibiting good mechanical properties (with 98GPa tensile moudulus) which compete with higher grade materials. This demonstrates the potential for high value applications for recovered carbon fibre by preferential fibre alignment. The fundamental theory of this hydrodynamic alignment process is similar to the paper making process: the fibre suspension flows through the headbox to form a moist paper sheet and then the water residual is removed in the forming section (vacuum suction), press section and drying section. However, the drying section takes 85% energy consumption of the whole dewatering process and a 1% reduction in sheet moisture after the vacuum dewatering results in a 4% reduction in dryer load. Thus, to reduce the energy costs, the optimization of vacuum dewatering is important in paper making process and this hydrodynamic alignment process. The dewatering behaviour of the aligned fibre mat is investigated in this thesis. As one of the main factors which can determine the dewatering rate, permeability was measured and predicted. Based on the predicted permeability, the required suction pressure in dewatering process for an aligned fibre mat with target areal density is evaluated. To maintain the suction pressure with a low energy cost, a pump selection analytical model is developed with the performance curves of liquid ring pump, high pressure radial blower and 2-stage channel blower. Furthermore, to increase the dewatering efficiency and protect the aligned fibre orientation, the evenly distributed vacuum pressure through the fibre mat is required. Therefore, in this thesis, the optimised opening geometry for the deposition drum is identified. The lay-up configuration of nylon meshes with different wire sizes was studied to raise the best pressure distribution media.